PEMBIAKAN TABANUS RUMDUS (DIPTERA : TABANIDAE) DI LABORATORIUM - HARTINI, SRI; AZIZ, JANITA (Research Center for Biology-Indonesian Institute of Sciences, 1986)
SRI HARTINI & JAMTA AZIZ. 1986. Rearing Tabanus rubidus (Diptera : Tabanidae) in the laboratory. Berita Biologi 3 (6) : 273 - 276. Horseflies Tabanus rubidus were reared in the laboratory under 27.5-°C room temperature. Flies from the field layed eggs 5.8 days (i-7 days) and hatching leaching 62.3%.The aquatic larvae required